Correlation between Seizure Characteristics and Quality of Life in Epilepsy Patients - Pinzon, Rizaldy Taslim; Sanyasi, Rosa De Lima Renita; Tandora, Jesisca; Wijono, Andre Dharmawan; Buwana, Fransiscus (Asian Journal of Medical Sciences, 2018)
Background: Epilepsy is one of the most common neurological disorder and characterized by recurrent seizures caused by abnormal electrical activity in the brain. Epilepsy is both a medical diagnosis and a social label that can negatively impact quality of life (QoL). Aims and Objective: This study aimed to evaluate the correlation between characteristics of seizure and QoL among epilepsy patients. Materials and Methods: This is a case series study conducted at Bethesda Hospital, Yogyakarta. Subjects answer 8 questions in the SF-8 questionnaire by choosing one from several alternative answers. Sub-scale assessed in this questionnaire including general health perception (GH), physical functioning (PF), physical role functioning (RP), bodily pain (BP), vitality (VT), social role function (SF), mental health (MH), and emotional role functioning (RE). Each answer will be score and processed in a program from Optum™. The final results will be summarized into physical component (PCS) and mental component (MCS). Results: Total of the subjects were 27. Subjects were dominated by male, age< 60 years. The highest score is on the bodily pain subscale (mean: 50.00 ± 8.0739), wherease the lowest score is on global health perception (mean: 43.95 ± 7.1970). Overall, subjects in this study have a better mental status than physical status (47.14 ± 10.2093 vs 46.90 ± 7.9418). Type of seizure (PCS p: 0.794; MCS p:0.093), duration of epilepsy(PCS p: 0.832; MCS p: 0.856), history of epileptic status (PCS p: 0.141; MCS p: 0.951), the presence of neurological deficit (PCS p: 0.140; MCS p: 0.283), frequency of seizure before treatment (PCS p: 0.648; MCS p: 0.213), frequency of seizure after treatment (PCS p: 0.249; MCS p: 0.407), and frequency of seizure within the last 1 year were not significant to influence the QoL (PCS p:0.978; MCS p: 0.513). Conclusion: There is no significant characteristics of seizure that influence the QoL. Asian Journal of Medical Sciences Vol.9(6) 2018 1-6